Modification of Kaolin Mineralogy and Morphology by Heat Treatment and possibility of Use in Geotechnical Engineering - Nurmunira, Muhammad; Ideris, Zakaria; Namdar, Abdoullah (GEOMATE International Society, 2013)
This paper presents an experimental work on the effect of heat treatment on the mineralogy and morphology of kaolin. Kaolin, which is moderately expansive, was preheated at temperatures ranging from 200°C to 800°C by increment of 200°C and cooled at room temperature before it was mixed with peat. Peat represents a compressible soil and has low bearing value. The main aim of the work is to study the effect of heat treatment on shear strength parameters of peat-kaolin mixture. The mixtures are prepared at different proportions, and at each proportion triaxial samples were prepared and tested in the undrained condition to study the shear strength parameters. Untreated kaolin-soil mix was also prepared to provide a comparison between the treated and untreated soil mix in terms of the shear strength behaviour. XRD and FESEM were also carried out to investigate the change in soil micro-structure due to heat treatment. The tests showed that there was a slight improvement in the strength of peat-kaolin mixture when kaolin was preheated to a temperature of up to 400°C. Finally results were discussed and conclusions were made for the preheated kaolin-peat mixture.